(3GSQGQ GdMjhO GdSOGSj (B:s (3GdWQjb ddMjhO GdSOGSj (B- (3GOGQI eTGQjY GdMjhO GdSOGSj (B/s - (3GdfGHdSj, GdegfOS egfOs ((3YeGf(B: s (3OGQ hGFd ddfTQ(B, s, 2005)
(3GdHYO GdehShYj ddMjhO GdSOGSj h GdWQjb Gdi GdMjhO GdSOGSj (B( (3GdeONd(B, (3GdJWHjb(B, (3GdNjGQGJ(B, (3BdjI Md GdeTGcd(B, DMAIC (3GdaQhbGJ eY GdLhOIGdTGedI(B, (3GdGOhGJ(B)(3; GVGaI Gdi GOGQI eTGQjY GdMjhO GdSOGSj(B: (3GdeQGMd GdSJ GdGSGSjI dJWHjb GdMjhO GdSjGSj h cPG YQV Tjb dGge JSY COhGJ eY LOhd JcGed cjajI bjGS caGAI GdYedjGJ h GNjQG eMGPjQ GdaTd aj eTGQjY GdMjhO GdSjGSj(B.s
Keywords: (3GOGQI GdGYeGds; (3GdGOGQIs; (3GdMjhO GdSOGSjs